2015
DOI: 10.1051/fruits/2015022
|View full text |Cite
|
Sign up to set email alerts
|

Bio-agronomic characterization of twelve plum cultivars on two clonal rootstocks in a semi-arid environment in Sicily

Abstract: -Introduction. Plum cultivation in Southern Italy is of great interest due to the possibility of obtaining produce over an extended period using early and late varieties. The objective of this study was to choose the best combination of cultivars and rootstock to make the production period as long as possible. Materials and methods. The influence of two rootstocks i.e. Myrobalan 29C (Prunus cerasifera Ehrn.) and Montclar r [Prunus persica (L.) Batsch] on growth, yield and fruit quality of nine Japanese and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
1
0
1
Order By: Relevance
“…The hexaploid European plums (Prunus domestica L.) and the diploid Japanese plums (Prunus salicina Lindl.) are among the most widely cultivated fruit species in temperate climates (Ferlito et al, 2015;Reig et al, 2018a). The commonly used rootstocks for European plum cultivars include different Prunus species such as Prunus cerasifera (Myrobalan or cherry plums, 2n=16), P. cerasifera x P. munsoniana hybrids (Marianna), P. spinosa (Sloe or blackthorn plums, 2n=32), P. insititia (Damson plums, 2n=48), and P. domestica (common plums, 2n=48).…”
Section: Introductionmentioning
confidence: 99%
“…The hexaploid European plums (Prunus domestica L.) and the diploid Japanese plums (Prunus salicina Lindl.) are among the most widely cultivated fruit species in temperate climates (Ferlito et al, 2015;Reig et al, 2018a). The commonly used rootstocks for European plum cultivars include different Prunus species such as Prunus cerasifera (Myrobalan or cherry plums, 2n=16), P. cerasifera x P. munsoniana hybrids (Marianna), P. spinosa (Sloe or blackthorn plums, 2n=32), P. insititia (Damson plums, 2n=48), and P. domestica (common plums, 2n=48).…”
Section: Introductionmentioning
confidence: 99%
“…U podnože Myrobalán B poukazují na nedokonalou afinitu s odrůdou asijské slivoně 'Ozark Premier' . Ferlito et al (2015) doporučují pro semi aridní prostředí jižní Itálie odrůdy asijských slivoní 'Obilnaja' a 'Shiro' v kombinaci s podnožemi Myrobalán 29C a Montclare. Sosna a Kortylewska (2010) publikovali výsledky hodnocení růstových a výnosových parametrů odrůd 'Kometa', 'Najdena', 'Skoroplodnaja' a 'Shiro' na podnoži Wangenheimova ve sponu 4 × 2 m (1 250 stromů na hektar).…”
Section: Doporučené Podnožeunclassified
“…The literature highlights the need for particular attention to vineyard management and therefore to the analysis of the life cycle delimited to the agricultural phase for grape production [15][16][17][18][19][20]. The research on the adoption of LCA in the wine sector has shown an unequivocal environmental hotspot in the agricultural phase [2] due to the wide use of different agronomic techniques [15][16][17][18][19][20], which require an extensive use of inputs [21].…”
Section: Environmental Impacts In the Agricultural Phasementioning
confidence: 99%
“…The scientific literature on the adoption of LCA in the agri-food sector has shown an unequivocal environmental hotspot in the agricultural phase [2]. The agricultural phase involves the adoption of different agronomic techniques, such as soil management, fertilization, weeding, irrigation, pruning and harvesting [15][16][17][18][19][20], which require a wide use of inputs such as fuel, fertilization, pesticides and water irrigation [21]. However, the transformation phase of wine production also generates environmental impact due to the packaging materials used [22].…”
Section: Introductionmentioning
confidence: 99%